Developing a conservation-based beach sports tourism model for sustainable coastal recreation - Muhammad Ali; Fadli Ihsan; Eval Edmizal (Indonesian Institute For Counseling, Education and Therapy, 2026)
Therefore, this study aimed to develop and evaluate a validated conservation-based beach sports tourism model that integrates eco-friendly sport activities, environmental education, community involvement, and zoning-based coastal management to enhance conservation awareness and support sustainable tourism in small island destinations. Materials and Methods: This study employed a Research and Development (R&D) design adapted from Borg and Gall, limited to four stages: research and information gathering, planning, preliminary model development, and preliminary field testing. The study involved 60 participants consisting of tourists, local community members, tourism managers, and experts selected through purposive sampling. Data were collected using observation, interviews, questionnaires, and documentation. Quantitative data were analyzed using descriptive statistics, normality and homogeneity tests, and paired sample t-tests, while qualitative data were analyzed thematically. The findings showed high demand for the proposed model (Mean = 4.32; 86.4%), high conservation awareness (Mean = 4.10; 82.0%), and strong feasibility ratings (Mean = 4.25; 85.0%). Model usability was also rated positively (Mean = 4.18; 83.6%). Conservation awareness significantly improved after implementation, increasing from pre-test (Mean = 3.65; 73.0%) to post-test (Mean = 4.10; 82.0%), with a mean difference of 0.45 points. Statistical analysis confirmed a significant improvement (t = 3.87, p < 0.001) with a moderate effect size (Cohen’s d = 0.65). Conclusions: The validated conservation-based beach sports tourism model was found to be feasible, practical, and effective in enhancing participants’ conservation awareness. Preliminary field testing demonstrated a significant improvement in conservation awareness, with mean scores increasing from 3.65 to 4.10 (t = 3.87, p < 0.001; Cohen’s d = 0.65). By integrating eco-friendly beach sports activities, environmental education, community participation, and zoning-based coastal management, the model provides a practical framework for promoting sustainable tourism development in small island destinations.